2011
DOI: 10.2147/ijn.s17626
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of single-walled carbon nanotube solubility by noncovalent PEGylation using experimental design methods

Abstract: In this study, noncovalent functionalization of single-walled carbon nanotubes (SWCNTs) with phospholipid-polyethylene glycols (Pl-PEGs) was performed to improve the solubility of SWCNTs in aqueous solution. Two kinds of PEG derivatives, ie, Pl-PEG 2000 and Pl-PEG 5000, were used for the PEGylation process. An experimental design technique (D-optimal design and second-order polynomial equations) was applied to investigate the effect of variables on PEGylation and the solubility of SWCNTs. The type of PEG deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…However, it is necessary to promote carbon nanotubes’ biocompatibility in a biological medium [ 52 ]. DSPE-PEG is one of the most used polymers with a suitable safety profile, and also improves the aqueous solubility of insoluble materials [ 45 , 53 ]. DSPE-PEG might be either adsorbed or covalently bonded to the surface of SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is necessary to promote carbon nanotubes’ biocompatibility in a biological medium [ 52 ]. DSPE-PEG is one of the most used polymers with a suitable safety profile, and also improves the aqueous solubility of insoluble materials [ 45 , 53 ]. DSPE-PEG might be either adsorbed or covalently bonded to the surface of SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Then, for homogenization, the suspension was sonicated on ice with an ultrasonic processor using 100% amplitude and 120 W power (UP200Ht Hielsher, Hielscher, Germany) for 2 min (20 s pulse and 10 s pause). To separate non-PEGylated SWCNTs from the supernatant, the suspension was centrifuged at 20,000 rpm (Beckman, IN, USA) at room temperature for 4 h. Finally, the DSPE-PEG (5000) amine/SWCNT concentration in the supernatants was determined by the spectrophotometric method at 280 nm [ 44 , 45 ]. A TNBSA test was performed to determine free amino groups on DSPE-PEG (5000) amine loaded onto SWCNTs [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A suitable modification on the surface of SWCNTs can help it get reliable dispersibility in physiologically relevant, aqueous environments and promote their biodistribution 28,29 . We used DSPE-PEG2000-amine to modify the SWCNT, which has been demonstrated to graft on SWCNT and improve the aqueous solubility of it, and furthermore, it showed excellent stability without agglomeration in biological media 30 . Sulfo-LC-SPDP was used as a crosslinker in the experiment, which helped functionalized SWCNT to bind the anti-MALAT1 gapmer DNA through disulfide linkage, and thereafter deliver them into cells.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of [ 29 , 30 ] reported that specific nanotubes may be less harmful than nano-carriers for drugs. It has also been shown that simple functionalization (-OH, -COOH, -NH, PEG) [ 31 ] or encapsulation of the CNTs [ 22 ], increases the water solubility, improves bioavailability, and reduces toxicity of CNTs. And the introduction of CNTs to mice with a transplanted tumor may be effective against targeted transformed tissue and led to decreasing of tumor volume and to increasing animal survival [ 32 ].…”
Section: Introductionmentioning
confidence: 99%